2014
DOI: 10.1111/odi.12253
|View full text |Cite
|
Sign up to set email alerts
|

Cell dynamics in Hertwig's epithelial root sheath and surrounding mesenchyme in mice irradiated to the head

Abstract: These results indicate that the early disappearance of HERS and the proliferative suppression of the surrounding mesenchymal cells, which was induced by irradiation, caused dental root malformation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Both environmental and genetic conditions may impair root development. A study in mice showed that radiation of 10 and 20 Grey before the onset of root development disrupted the HERS and gave root malformation 17 . A genetic study using Nuclear factor I-C (Nfic) knockout mice demonstrated disturbances in root patterning leading to taurodontism in these mice 18 .…”
Section: Discussionmentioning
confidence: 99%
“…Both environmental and genetic conditions may impair root development. A study in mice showed that radiation of 10 and 20 Grey before the onset of root development disrupted the HERS and gave root malformation 17 . A genetic study using Nuclear factor I-C (Nfic) knockout mice demonstrated disturbances in root patterning leading to taurodontism in these mice 18 .…”
Section: Discussionmentioning
confidence: 99%
“…Computerized 3D reconstruction was performed using 3D analytic software (TRI/3D-BON; Ratoc System Engineering, Tokyo, Japan). The first molars were extracted and spuriously stained upon the slice image, as described previously by Ide [ 24 ]. Thereafter, 3D reconstruction of the tooth images was performed.…”
Section: Methodsmentioning
confidence: 99%